The quality of indonesian brands of consumable cooking oils is reviewed by peroxide numbers and free fatty acid value - Anggarani, Mirwa Adiprahara; Wikandari, Prima Retno; Agustini, Rudiana; Waskito, Rusyariyanto; Fransiska, Yuni (Pascasarjana Universitas Negeri Medan, 2024)
This study evaluated laboratory skills among the students during biochemistry practicum activities and built laboratory information for the internal and external community of Universitas Negeri Surabaya in 2024. The habit of reusing cooking oil for the main reason of saving costs can cause health problems. Parameters used to determine quality cooking oils include content-free fatty acids and number peroxide. The research purposes for this experiment are to know the rate of free fatty acids and the number of peroxides in Branded and out-of-stock cooking oil used for now. Determination of free fatty acids was done with the method of alkalimetry and the determination number of peroxide was done with the technique of iodometry. Result of the study This shows average rate of sour fat-free oil frying before frying is 0.22% And after frying becomes 0.40% or enhancement amounting to 185.98 %. The average level of number peroxide oil fried before frying is as big as 1.11 meq O2 /kg and after frying to 3.52 meq O2 /kg or enhancement as big as 317.25%. Average rate sour fat-free oil fry before frying No exceed standard SNI 7702: 2012, namely maximum 0.3%. However, the average level of free fatty acids in cooking oil after frying exceeds the SNI 7702:2012 standard, namely above 0.3%. Whereas the average rate number peroxide oil fry before and after frying does not exceed standard SNI 7709: 2012 which is a maximum of 10 meq O2 /kg.